Estudio de las políticas públicas y su incidencia para combatir la pobreza en la parroquia rural de Ricaurte - Pinargote Mejía, Luber José (2025)
This study analyzed the effectiveness of public policies implemented by the Decentralized Autonomous Parish Government in Ricaurte Parish in reducing poverty. A methodology based on inductive, deductive, and analytical-synthetic methods was applied, using bibliographic, field, and descriptive research types. Techniques included surveys, interviews, and document analysis. Dimensions such as access to basic services, employment, education, and citizen participation were evaluated. The results indicated that although progress was made in basic infrastructure such as potable water, electricity, and sanitation, deficiencies persist in resource management, institutional transparency, and community inclusion in policy formulation. A considerable portion of the population expressed negative perceptions regarding the accessibility and effectiveness of government actions. Low citizen participation in decision-making was evident, limiting the impact of the implemented strategies. In conclusion, the study established the need to strengthen participatory governance mechanisms, improve interinstitutional coordination, and ensure the sustainability of implemented programs. It also recommended aligning local policies with national and international regulatory frameworks to achieve equitable development that can be replicated in other rural areas.